2011
DOI: 10.1017/s0007114511002686
|View full text |Cite
|
Sign up to set email alerts
|

Soya protein- and casein-based nutritionally complete diets fed during gestation and lactation differ in effects on characteristics of the metabolic syndrome in male offspring of Wistar rats

Abstract: The AIN-93G diets based on soya protein or casein were fed to pregnant Wistar rats from day 3 of gestation and compared for their effects on characteristics of the metabolic syndrome in male offspring. Pregnant rats were randomised to either a casein (C) or soya protein (S) diet (n 12) during gestation only (Expt 1) or during gestation and lactation (Expt 2). Male offspring were weaned to either a C or S diet for 9 weeks (Expt 1) or 15 weeks (Expt 2). In Expt 1, pups born to S-fed dams had higher fasting blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 54 publications
(64 reference statements)
3
48
0
Order By: Relevance
“…F 0 animals fed these diets only during the post-weaning period did not show significant differences in body weights from the natural ingredient diets or from the AIN-93 group, indicating that the diet consumed by the dam during gestation and lactation influenced the pup body weights. The importance of the diet consumed by the dam on pup body weight throughout life has been reported in other studies of soy- versus casein-containing diets, although inconsistent effects have been found, with the soy-consuming F 1 CD-1 mice having lower body weights (Cederroth et al, 2007; Ruhlen et al, 2008) and Wistar rats having higher body weights (Jahan-Mihan et al, 2011; Jahan-Mihan et al, 2012). A study in Sprague-Dawley rats reported no differences in adult body weight between rats fed purified diets with either casein or soy protein isolate as the protein sources (Badger et al, 2001).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…F 0 animals fed these diets only during the post-weaning period did not show significant differences in body weights from the natural ingredient diets or from the AIN-93 group, indicating that the diet consumed by the dam during gestation and lactation influenced the pup body weights. The importance of the diet consumed by the dam on pup body weight throughout life has been reported in other studies of soy- versus casein-containing diets, although inconsistent effects have been found, with the soy-consuming F 1 CD-1 mice having lower body weights (Cederroth et al, 2007; Ruhlen et al, 2008) and Wistar rats having higher body weights (Jahan-Mihan et al, 2011; Jahan-Mihan et al, 2012). A study in Sprague-Dawley rats reported no differences in adult body weight between rats fed purified diets with either casein or soy protein isolate as the protein sources (Badger et al, 2001).…”
Section: Discussionmentioning
confidence: 71%
“…Developmental exposure of Wistar rats to soy protein-containing diet was reported to increase body weight of both male and female rats as adults compared to those fed a casein diet, but glucose intolerance was more pronounced in adult males (Jahan-Mihan et al, 2011). The effects of the dietary protein difference were largely attributed to the dams’ diet during pregnancy (Jahan-Mihan et al, 2012). The data regarding soy diet effects on body weight and obesity are thus somewhat difficult to interpret and may depend on species and strain, the specific soy preparations or components examined, or other diet constituents or properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Food intake was also higher in offspring born to dams fed soy protein diet in PW period . These data indicate that even in a nutritionally balanced diet fed during gestation and lactation, the source of protein can influence the risk of MS in the offspring .…”
Section: Introductionmentioning
confidence: 64%
“…Rats were fasted overnight for 12 h. Blood samples were drawn from the tail vein at fasting and at 15, 30 and 60 min after a glucose administration (0.375 g glucose per mL, 5 g glucose per kg BW) .…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation